Impact of the 2016 ASE/EACVI recommendations on the prevalence of diastolic dysfunction in the general population - Almeida, JG (2017)
Aims: Diastolic dysfunction (DD) is frequent in the general population; however, the assessment of diastolic function remains challenging. We aimed to evaluate the impact of the recent 2016 American Society of Echocardiography (ASE)/European Association of Cardiovascular Imaging (EACVI) recommendations in the prevalence and grades of DD compared with the 2009 guidelines and the Canberra Study Criteria (CSC). Methods and results: Within a population-based cohort, a total of 1000 individuals, aged ≥45 years, were evaluated retrospectively. Patients with previously known cardiac disease or ejection fraction <50% were excluded. Diastolic function was assessed by transthoracic echocardiography. DD prevalence and grades were determined according to the three classifications. The mean age was 62.0 ± 10.5 years and 37% were men. The prevalence of DD was 1.4% (n = 14) with the 2016 recommendations, 38.1% (n = 381) with the 2009 recommendations, and 30.4% (n = 304) using the CSC. The concordance between the updated recommendations and the other two was poor (from k = 0.13 to k = 0.18, P < 0.001). Regarding the categorization in DD grades, none of the 14 individuals with DD by the 2016 guidelines were assigned to Grade 1 DD, 64% were classified as Grade 2, 7% had Grade 3, and 29% had indeterminate grade. Conclusion: The application of the new 2016 ASE/EACVI recommendations resulted in a much lower prevalence of DD. The concordance between the classifications was poor. The updated algorithm seems to be able to diagnose only the most advanced cases.